2016
DOI: 10.3906/mat-1503-12
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Bertrand Curves with Spacelike $\left(1,3\right) $-Normal Plane in Minkowski Space-Time

Abstract: Abstract:In this paper, we reconsider the (1, 3) -Bertrand curves with respect to the casual characters of a (1, 3) -normal plane that is a plane spanned by the principal normal and the second binormal vector fields of the given curve. Here, we restrict our investigation of (1, 3) -Bertrand curves to the spacelike (1, 3) -normal plane in Minkowski space-time. We obtain the necessary and sufficient conditions for the curves with spacelike (1, 3) -normal plane to be (1, 3) -Bertrand curves and we give the relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…3-space and Minkowski space-time (see [1,2,7,11,[24][25][26]28]) as well as in Euclidean space. In addition, in [27,30], the authors studied (1, 3)-type Bertrand curves in semi-Euclidean 4-space with index 2.…”
Section: Introductionmentioning
confidence: 99%
“…3-space and Minkowski space-time (see [1,2,7,11,[24][25][26]28]) as well as in Euclidean space. In addition, in [27,30], the authors studied (1, 3)-type Bertrand curves in semi-Euclidean 4-space with index 2.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these curves mates have been generalized to larger dimensions and have been studied by many authors [11,17,19,28,35]. Also, these pairs of curves have been studied by many authors in the Lorentzian space [3,5,16,18,21,24,34,40,41,43].…”
Section: Introductionmentioning
confidence: 99%
“…İlarslan et al have defined null Cartan and pseudo null Bertrand curves in Minkowski 3-space E 3 1 [6]. Further, (1,3)-Bertrand curves in a timelike (1,3)-normal plane in Minkowski space-time E 4 1 have been examined [7]. Also, Matsuda and Yorozu have shown that there is no Bertrand curve in Euclidean n-space E n such that n ≥ 4 and have defined (1,3)-Bertrand curves in Euclidean 4-space E 4 [8].…”
Section: Introductionmentioning
confidence: 99%